Between adaption and rejection: intergenerational transmission ofrResources and work values in Germany - Strohmeyer, Robert; Weiß, Julia (Intergenerational transmission and economic self-sufficiency, 2023)
This chapter discusses the intergenerational transmission of resources and work values from parents to the offspring. Semi-structured biographical interviews with ten families from Southern Germany revealed the following main transmission mechanisms: role models, parenting style, and social capital. Children viewed parents as their models and imitated the observed behaviors. The parenting style had a decisive influence on the successful child outcomes. Parents’ social networks proved to be yet a crucial factor determining the child’s success.
Gesehen am 19.06.2023